TEORI OLIGARKI WINTERS ATAS PENAMBANGAN BATUBARA DI KALIMANTAN TIMUR (RELASI PENGUSAHA MENJADI PENGUASA) - Febriani, Anita; Istanti, Dilla Janu; Wibowo, Ponco (Jurnal Ilmiah Widya Sosiopolitika, 2021)
Oligarchy portrait occurs in the process of coal mining in East Kalimantan. Many of the power-holding elites are involved in collaborating to become a mining resource chain in East Kalimantan. The Sexi Killer film by WatchDoc Documentary provides an illustration that explains how the elite was involved in becoming coal mining players in East Kalimantan. Coal mining does not necessarily bring prosperity to the surrounding community but instead brings about various environmental disasters. Several names of the ruling elite were dragged into the circle of mining business practices. Jefri A. Winters' oligarchic theory can explain why this portrait can occur. Democracy seems to have slipped in an oligarchy circle. The elite control material resources to increase wealth and maintain its social means. Keywords: Elite, Oligarchy, Kalimantan Coal Mining.